Molecular biology of normal melanocytes and melanoma cells. Issue 8 (23rd March 2013) - Bandarchi, Bizhan; Jabbari, Cyrus Aleksandre; Vedadi, Ali; Navab, Roya
Abstract : Malignant melanoma is one of the most aggressive malignancies in humans and is responsible for 60–80% of deaths from skin cancers. The 5-year survival of patients with metastatic malignant melanoma is about 14%. Its incidence has been increasing in the white population over the past two decades. The mechanisms leading to malignant transformation of melanocytes and melanocytic lesions are poorly understood. In developing malignant melanoma, there is a complex interaction of environmental and endogenous (genetic) factors, including: dysregulation of cell proliferation, programmed cell death (apoptosis) and cell-to-cell interactions. The understanding of genetic alterations in signalling pathways of primary and metastatic malignant melanoma and their interactions may lead to therapeutics modalities, including targeted therapies, particularly in advanced melanomas that have high mortality rates and are often resistant to chemotherapy and radiotherapy. Our knowledge regarding the molecular biology of malignant melanoma has been expanding. Even though several genes involved in melanocyte development may also be associated with melanoma cell development, it is still unclear how a normal melanocyte becomes a melanoma cell. This article reviews the molecular events and recent findings associated with malignant melanoma.